MICROBIAL PATTERNS OF HOSPITALIZED HIV POSITIVE PATIENTS ADMITTED IN DR. SOETOMO GENERAL HOSPITAL, SURABAYA INDONESIA - Tan, Feriawan; Triyono, Erwin Astha; Wahyunitisari, Manik Retno (Journal of Vocational Health Studies, 2021)
Background: HIV patients with a weak immune system are very vulnerable to opportunistic infections, can trigger systemic endothelial activation and end up as a condition of sepsis. In Indonesia currently, there is no bacterial epidemiological mapping of the etiology of opportunistic infections in HIV patients. Purpose: To determine the pattern of bacteria that cause opportunistic infections and their antibiotic sensitivity in HIV patients. Method: Prospective observational study design. Data were obtained from medical records of hospitalized patients at RSUD Dr. Soetomo Surabaya from August 2019 - February 2020. Result: Out of 64 patients, 83 specimens were found with the most types of gram-negative bacteria 44.6%, while gram-positive bacteria were 15.7% and a mix of 2.4% and 37.3% negative culture. The highest prevalence of gram-negative bacteria was Klebsiella pneumoniae (35.15), followed by Escherichia coli (10.8%), Pseudomonas aeruginosa (8.1%), and Acinetobacter baumanii (8.1%). The highest prevalence of gram-positive bacteria was Streptococcus mitis / oralis (30.7%), followed by Staphylococcus aureus (23.1%) and Staphylococcus epidermidis (15.4%). Among gram-negative bacteria antibiotic, Cefoperazone-sulbactam showed the greatest sensitivity, following by Amikacin, Gentamycin and Piperacillin-tazobactam; while among gram-positive bacteria are Chloramphenicol, Linezolid, and Vancomycin. Almost all isolates showed resistance to Ampicillin. Conclusion: Bacteria pattern that caused opportunistic infection in RSUD Dr. Soetomo is K. pneumonia as most common gram-negative bacteria followed by E. coli, P. aeruginosa and A. baumanii; while the most gram-positive bacteria found are S. mitis/oralis and S. aureus. Among antibiotic used, Ampicillin showed the lowest sensitivity to almost all bacteria isolates.